2002
DOI: 10.1902/jop.2002.73.8.886
|View full text |Cite
|
Sign up to set email alerts
|

Eikenella corrodens in Subgingival Plaque: Relationship to Age and Periodontal Condition

Abstract: Since the distribution of E. corrodens is significantly higher in JP, post-JP, and PP, E. corrodens might play an important role in the occurrence or progression of periodontitis in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…E. corrodens has been associated with adult gingivitis (Ashimoto et al, 1996), prepubertal periodontitis (Delaney and Kornman, 1987), chronic periodontitis (Ximenez-Fyvie et al, 2000a) and aggressive forms of periodontitis (Suda et al, 2002). On the other hand Albandar et al (1997) showed that E. corrodens was present equally in subjects with and without early-onset periodontitis.…”
Section: Article In Pressmentioning
confidence: 99%
“…E. corrodens has been associated with adult gingivitis (Ashimoto et al, 1996), prepubertal periodontitis (Delaney and Kornman, 1987), chronic periodontitis (Ximenez-Fyvie et al, 2000a) and aggressive forms of periodontitis (Suda et al, 2002). On the other hand Albandar et al (1997) showed that E. corrodens was present equally in subjects with and without early-onset periodontitis.…”
Section: Article In Pressmentioning
confidence: 99%
“…Prema ovome, odnos vrednosti 17β estradiol u serumu i inflamacije gingive je the findings of several authors who suggest an increased trend of gingival disorder in girls during puberty maturation 2,15,25 , which depends on the fluctuating levels of sex hormones, age, bacterial composition of dental plaque, inflammatory cell response, vascular reactions, morphological differences, etc 30,31 . During puberty, an increased gingival bleeding index significantly grows with development of puberty, while significant downward trend is seen after 14 years of age for girls 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Zbog nedostatka adekvatnih istraživanja, koja će istražiti uticaj polnih hormona na zdravlje gingive, u ovom istraživanju tačno je određen nivo polnog hormona estradiola 17β u serumu i pljuvački i njegov odnos sa gingivalnim indeksom. Rezultati eksperimentalne grupe pokazali su prisutnu inflamaciju gingive, koja je u skladu sa nalazima drugih autora koji ukazuju na inflamaciju gingive kod devojčica u pubertetu 2,15,25 , koja zavisi od promenjenih nivoa polnih hormona, starosti, bakterijskog sastava oralnog biofilma, inflamatornog odgovora ćelija, vaskularne reakcije, morfološke razlike itd 30,31 . Istraživači ističu da je u pubertetu povećan gingivalni indeks, koji značajno raste sa razvitkom puberteta, a njegov pad je uočen posle 14 godina kod devojčica 15,25 .…”
Section: Discussionunclassified
See 2 more Smart Citations